2020
DOI: 10.1088/1748-9326/ab6d39
|View full text |Cite
|
Sign up to set email alerts
|

Observed earlier start of the growing season from middle to high latitudes across the Northern Hemisphere snow-covered landmass for the period 2001–2014

Abstract: Vegetation phenology in spring has received much attention for its importance to terrestrial ecosystem carbon exchange and climate-biosphere interactions studies. Through control on surface water and heat balance, snow cover largely impacts on spring vegetation phenology. However, under the background of global warming and rapid reduction of spring snow cover extent across the Northern Hemisphere (NH), the responses of spring vegetation phenology have not been well documented. Using two satellite-derived land … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 56 publications
0
17
0
1
Order By: Relevance
“…Accompanied by SOS monitoring, the attribution of SOS anomalies has also drawn great attention in the past few years. Published studies have reported that global climate change is a primary driver of SOS variations in terrestrial ecosystems [37][38][39][40][41][42][43][44]. Several variables are attributed to SOS anomalies, e.g., land-surface temperature (T s ) [42,[44][45][46], total precipitation (P t ) [46], water availability [40], spring snow-cover anomalies [43,44], and photoperiod [46][47][48] and temperature sensitivity [7,49] changes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accompanied by SOS monitoring, the attribution of SOS anomalies has also drawn great attention in the past few years. Published studies have reported that global climate change is a primary driver of SOS variations in terrestrial ecosystems [37][38][39][40][41][42][43][44]. Several variables are attributed to SOS anomalies, e.g., land-surface temperature (T s ) [42,[44][45][46], total precipitation (P t ) [46], water availability [40], spring snow-cover anomalies [43,44], and photoperiod [46][47][48] and temperature sensitivity [7,49] changes.…”
Section: Introductionmentioning
confidence: 99%
“…Published studies have reported that global climate change is a primary driver of SOS variations in terrestrial ecosystems [37][38][39][40][41][42][43][44]. Several variables are attributed to SOS anomalies, e.g., land-surface temperature (T s ) [42,[44][45][46], total precipitation (P t ) [46], water availability [40], spring snow-cover anomalies [43,44], and photoperiod [46][47][48] and temperature sensitivity [7,49] changes. Among the abovementioned driving factors, T s , P t , and snow cover are basic and representative variables.…”
Section: Introductionmentioning
confidence: 99%
“…Increases in vegetation for northern latitudes have been documented using satellite data since the 1980s (Bokhorst et al, 2009;Liu et al, 2015;Merrington, 2019;Raynolds et al, 2015;Slayback et al, 2003). Increases in the NDVI were found to be correlated with increases in summer surface temperature in most parts of the Arctic (Chen & Yang, 2020;Elmendorf et al, 2012;Wang et al, 2020). From 1990 to 2010, a straightforward relationship between plant and climate change has been revealed, with increasing temperatures causing higher vegetation productivity and, at the same time, being the reason for the longer growing seasons (De Beurs & Henebry, 2010;Li et al, 2020;Zhou, 2020).…”
Section: Introductionmentioning
confidence: 96%
“…Snow cover phenology (SCP) variables including snow onset date (D o ), snow end date (D e ), and snow duration days (D d ) are key indicators of seasonal variation of terrestrial snow cover over the NH and becoming increasingly valuable indicators of climate change [6,8], especially in snow-dominated cold regions [6,9]. For example, SCP has considerable impact on climate variabilities, such as alpine vegetation growth dynamics on the Tibetan Plateau [10], green-up date across the NH [11], boreal springtime carbon uptake [12], permafrost degradation in sub-arctic Sweden [9], and SCP indicators are expected to provide feedback to temperature trends [13]. Moreover, abnormal snowmelt timing in spring are creating a serious threat to water resource sustainability, including agricultural production [14] and even cause hydrological extremes such as spring floods [15].…”
Section: Introductionmentioning
confidence: 99%